Effects of dietary fibre intake on risk factors for cardiovascular disease in subjects at high risk. Issue 7 (15th March 2009) - Estruch, R; Martínez-González, M A; Corella, D; Basora-Gallisá, J; Ruiz-Gutiérrez, V; Covas, M I; Fiol, M; Gómez-Gracia, E; López-Sabater, M C; Escoda, R; Pena, M A; Diez-Espino, J; et al.
Abstract : Background: Epidemiological studies and feeding trials with supplements suggest that fibre intake is associated with a reduction in cardiovascular risk. However, the effects of changes in dietary fibre on risk factor levels have not been evaluated in free-living individuals. Thus, the effects of changes in dietary fibre intake on cardiovascular risk factors were assessed over 3 months in free-living high-risk subjects. Methods: 772 high-risk subjects (age 69±5 years) were assigned to a low-fat diet or two Mediterranean-style diets. All participants received behavioural and nutritional education, including recommendations for increasing the consumption of vegetables, fruits, and legumes. Changes in food and nutrient intake, body weight, blood pressure, lipid profiles, glucose control and inflammatory markers were evaluated. Results: Most participants increased consumption of vegetable products, but the increase in dietary fibre exhibited wide between-subject variability (6–65 g/day). Body weight, waist circumference, and mean systolic and diastolic blood pressure decreased across quintiles of fibre intake (p<0.005; all). Reductions in fasting glucose and total cholesterol levels, and increments in HDL cholesterol were highest among participants in the upper 20% of fibre intake (p = 0.04 and 0.02 respectively). Plasma concentrations of C-reactive protein, but not those of inflammatory cytokines, decreased in parallel with increasing dietary fibre (p = 0.04). Significant reductions in LDL cholesterol were observed only among participants with the greatest increases in soluble fibre intake (p = 0.04). Conclusions: Increasing dietary fibre intake with natural foods is associated with reductions in classical and novel cardiovascular risk factors in a high-risk cohort.